PENGARUH MANAJEMEN KELAS DAN PERILAKU BELAJAR TERHADAP TINGKAT PEMAHAMAN SISWA SMKN 1 PONTIANAK - Silaban, Greace Lam Ria (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This study aims to examine and discuss the phenomena of classroom management and student learning behavior while in learning and to the level of understanding of accounting cycle class XI AK SMK Negeri 1 Pontianak. This research use associative method, and sample of this research is counted 100 student class XI academic year 2016/2017. Data collection techniques used are: (1) Indirect Communication Techniques (2) Direct Communication Techniques. While the data collection tool is: (1) Questionnaire research, (2) Interview guide. The results of this study indicate that: (1) There is partial influence of class management on the level of students' understanding of class XI AK SMK Negeri 1 Pontianak with the value of sig 0.001 <0.050. (2) There is partial influence of learning behavior toward level of understanding of student of class XI AK SMK Negeri 1 Pontianak with value of sig 0,036 <0,050. (3) There is a linear influence between classroom management on learning behavior with deviation from linierity 0,073> 0,050 siginifikansi value. (4) There is significant and positive influence simultaneously class management and learning behavior toward student understanding level shown from SPSS resume table obtained significance value 0,002 <0,050, and big influence of determination coefficient (R²) equal to 35%. Keywords: Classroom Management, Learning Behavior, Level Of understanding